The impact of generational change and retirement on psychiatry to 2025 - Schofield Deborah J; Fletcher Susan L (BMC, 2007)
Abstract Background Australia is currently experiencing widespread shortages of psychiatrists. The changing nature of the workforce and increasing demand mean that these shortages are unlikely to ease. This study aims to identify demographic change and retirement patterns of the Australian psychiatry workforce from 1995 to 2003, and the implications of those changes for future workforce planning. Methods Data from the Australian Institute of Health and Welfare (AIHW) Medical Labour Force Survey from 1995 to 2003 is used to examine ageing of the psychiatry workforce and attrition of psychiatrists aged 50 years and over. Future attrition from the workforce is projected to 2025. Results Sixty two percent of psychiatrists practicing in the year 2000 are predicted to have retired by 2025. Most psychiatrists continue to work until late in life, with only 18 per cent retiring before age 65. The psychiatry workforce aged significantly between 1995 and 2003 (p < 0.001), with men older than women in both years. A reduction in hours worked by psychiatrists reflects both the increasing proportion of females and the older members of the profession reducing their hours in preparation for retirement. Conclusion The impact of ageing of the workforce may be more immediate for psychiatry than for some other health professions. With the growing proportion of females and their typically lower workforce participation, more than one younger psychiatrist will be required to replace each of the mostly male retirees.